Risk, Readiness and Reception: Explaining Acceptance of Risk-Based Business Licensing Through the Technology Acceptance Model - Ni Komang Ayu Novitasari; Ni Luh Yulyana Dewi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study aims to analyze the acceptance of the risk-based business licensing system through the Online Single Submission Risk-Based Approach (OSS-RBA) by business actors in Bali Province using the Technology Acceptance Model (TAM) framework. The implementation of OSS-RBA has shown significant growth in the issuance of Business Identification Numbers (NIB) from 19,468 in 2021 to 108,365 in 2024. However, the gap between the number of operating businesses and those with formal legality remains significant, given that the total number of SMEs in Bali Province reached 448,434 units in 2024. This study employs a descriptive qualitative approach with data collection techniques including semi-structured interviews, non-participant observation, and documentation involving 30 informants selected through purposive and snowball sampling. Data analysis was conducted using the Miles and Huberman interactive model. Five TAM constructs were used as analytical frameworks: perceived usefulness, perceived ease of use, attitude toward use, behavioral intention to use, and actual system use. The findings indicate that OSS-RBA acceptance is varied, influenced by the digital capacity of business actors and the level of business risk. Perceived usefulness tends to be high, particularly among low-risk business actors. Perceived ease of use is affected by the complexity of technical requirements, including the need for polygon data requiring spatial mapping competency and additional cost implications. Additionally, the practice of using third-party services (proxy use) was identified, reflecting structural dynamics in system utilization. This research contributes to TAM development in the e-government context by highlighting the importance of contextual factors in supporting the optimization of risk-based licensing system implementation.